Prehypertension: is it a real medical problem? - Yoga Yuniadi (The Indonesian Heart Association, 2012)
The term of prehypertension is introduced in guideline of hypertension management released byJoint National Committee on Hypertension a decade back. Prehypertension is define as blood pressure of 120-139/80-89 mmHg which was clasified as high normal group in previous classification.Such intentional identification of patients as â€œprehypertensiveâ€ calls needed attention to the excess risk associatedwith BP in this range and reminds healthcare providers to pay more attention to prevention. However, is it really worth to pay more attention on prehypertension?